STUDI KOMPARATIF PENGATURAN SISTEM KEPARTAIAN DI INDONESIA - Yusdar AM (Al-Adalah: Jurnal Hukum dan Politik Islam, 2018)
This study aims to know and analyze the party system in Indonesia and compare then with party system in various countries. This type of research is a normative legal research. The approach used is the approach of legislation, conceptual approach and case approach. The result of the research shows that the construction of party system arrangement in Indonesia shows the inconsistent arrangement and the existence of repetition of norm to formulation of legislation related to party and the implementation of parliamentary threshold as effort to create simple multi party is considered failed because facts happened in election 2014 with parliamentary threshold 3,5% resulted in 10 political parties in parliament, in contrast to the 2009 elections with a 2.5% parliamentary threshold that resulted in 9 political parties in parliament.